2019
DOI: 10.1002/ped4.12127
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease shock syndrome: A report of two cases and literature review

Abstract: Importance Kawasaki disease shock syndrome (KDSS) is a rare Kawasaki disease (KD) manifestation. The pediatricians are not aware of the full range of clinical characteristics of KDSS. Objective We aimed to investigate the clinical features, diagnosis and treatment of KDSS in two patients and we included a literature review. Methods We collected and analyzed the clinical data for two patients with KDSS. Additionally, using “Kawasaki diseases shock syndrome” as a key phrase, we searched PubMed, Biotechnology Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In 1975, Kato et al [6] reported a case of severe complications such as shock and heart failure in a 6-monthold child with KD. Since then, this critically ill KD with hemodynamic changes has been reported by successive investigators [7][8][9][10][11]. In 2009, Kanegaye et al [12] first formally defined hemodynamically unstable Kawasaki disease as Kawasaki disease shock syndrome (KDSS), which accounts for approximately (1.9∼7.0)% of all KD.…”
Section: Introductionmentioning
confidence: 99%
“…In 1975, Kato et al [6] reported a case of severe complications such as shock and heart failure in a 6-monthold child with KD. Since then, this critically ill KD with hemodynamic changes has been reported by successive investigators [7][8][9][10][11]. In 2009, Kanegaye et al [12] first formally defined hemodynamically unstable Kawasaki disease as Kawasaki disease shock syndrome (KDSS), which accounts for approximately (1.9∼7.0)% of all KD.…”
Section: Introductionmentioning
confidence: 99%
“…These patients are often misdiagnosed as toxic shock syndrome (TSS) and this led to delays in institution of appropriate therapy (66,67). KDSS is usually seen in older children and is more commonly reported in boys (66,68,69), although some studies have also noted a female predominance (70). Some authorities believe that KDSS may, in fact, be a unique subtype of KD (65).…”
Section: Kd Shock Syndrome (Kdss)mentioning
confidence: 99%